2016
DOI: 10.1259/bjr.20160537
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and predictive values of diffusion and perfusion MRI in paediatric intracranial ependymomas in a large national study

Abstract: Objective: To assess the relative cerebral blood volume (rCBV) and apparent diffusion coefficient (ADC) derived, respectively, from perfusion and diffusion pre-operative MRI of intracranial ependymomas and their predictive and prognostic values. Methods: Pre-operative MRI and clinical data for intracranial ependymomas diagnosed between January 2000 and December 2013 were retrospectively retrieved from a web-based national database. MRI data included diffusion (62 patients) and perfusion (20 patients) MRI. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 19 publications
3
11
0
Order By: Relevance
“…The current study demonstrated that on DWI, almost all solid tissues of SAEs appeared hyperintense, whereas IAEs exhibited iso-hypointense signals. This result conformed to the histological and clinical outcome differences between SAEs and IAEs (1,10,16,22). Peritumoral edema commonly occurred when parenchymal involvement was noted.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The current study demonstrated that on DWI, almost all solid tissues of SAEs appeared hyperintense, whereas IAEs exhibited iso-hypointense signals. This result conformed to the histological and clinical outcome differences between SAEs and IAEs (1,10,16,22). Peritumoral edema commonly occurred when parenchymal involvement was noted.…”
Section: Discussionsupporting
confidence: 84%
“…Diffusion restriction was regarded as a characteristic of high-grade tumors and poorer prognostic factors for clinical outcome (10,25). The current study demonstrated that on DWI, almost all solid tissues of SAEs appeared hyperintense, whereas IAEs exhibited iso-hypointense signals.…”
Section: Discussionsupporting
confidence: 51%
“…Other studies have demonstrated the advantage of combinations of DWI, DSC perfusion, MR spectroscopy, and PET data in studying pediatric brain tumors. [18][19][20] To our knowledge, this is the first study to demonstrate a multiparametric approach using DCE and ADC histogram metrics in pediatric brain tumors.…”
Section: Discussionmentioning
confidence: 96%
“…8 Perfusion MRI may display elevated cerebral blood volume values and have some prognostic value. 18 Spinal cord ependymomas display more distinct borders than diffuse astrocytomas. 14 Cyst formation and T2 hypointensity of the cyst wall due to blood products ("hemosiderin cap") are suggestive of ependymoma.…”
Section: Clinical and Neuroimaging Diagnosismentioning
confidence: 99%